TOXICITY OF ETHANOLIC EXTRACT OF FRUIT, SEED AND LEAVES OF MAKUTADEWA (Phaleria macrocarpa (Scheff.) Boerl.) TO Artemia salina Leach AND THIN LAYER CHROMATOGRAM PROFILE OF ACTIVE EXTRACT - Indah Purwantini; Erna Prawita Setyowati; Triana Hertiani (Indonesian Journal of Pharmacy, 2002)
A research has been done to determine the toxicity of ethanolic extract of fruit, seed and leaves of makutadewa (Phaleria macrocarpa (Scheff) Boerl.) using Brine Shrimp Lethality Test method. Extract were made by maceration of the materials for 24 hours. The bioassay has been done using 48 hour old Artemia saline Leach. The effect of ethanolic extract was identified by determining and analysing the shrimp death percentage and LC50 of each extract using probit analysis.The result showed that these ethanolic extract were toxic to the shrimp. The ethanolic extract of seed was the most active with the LC50 of 1.60 x 102 g/ml, whereas that of the fruit has the LC50 of 30.42 g/ml. The thin layer chromatogram profile of the active extract suggested that the extract contains alkaloids.Key words : toxicity, makutadewa, brine shrimp lethality test